PM.62 Five Year Retrospective Review of Antenatal Lamivudine (LAM) to Reduce the Perinatal Transmission of Hepatitis B (HBV). (26th April 2013) - Ali, AA; Glennon, KG; Kelleher, BK; Eogan, ME; Jackson, VJ; Brennan, MB; Lawless, ML; Ferguson, WF; Lambert, JL
Abstract : Objectives: To review the safety and efficacy of LAM in reducing the perinatal transmission of HBV. Methods: Medical charts of HBV positive women who received treatment with LAM and who booked for antenatal care between 2007 and 2012 were retrospectively reviewed. Results: Between 2007 – 2012, 34 pregnant HBV positive women received treatment with LAM during the third trimester. All were HbeAg positive, and 6/34 were anti-HbCore IgM positive, indicative of acute infection. Where tested, the predominant genotypes were B and C, occurring in 16/32 and 11/32 respectively. Genotype D was noted in 4/32 women. One woman was co-infected with Hepatitis C. Mean viral load (VL) pre-treatment was >1 × 108 IU/ml, mean VL closest to delivery was 6.5 × 106 IU/ml (P < 0.001). No resistance to LAM was identified in the 70% who were tested post treatment. Median delivery gestation was 39 weeks (range 37–41 weeks); 17/33 had a normal vaginal delivery, 5/33 had an instrumental delivery, 9/33 had a C section, 2 delivered elsewhere and one patient is still pregnant. Median birth weight was 3.49 kg (range 2.33–4.72 kg). All babies received HBV IgG and the first dose of vaccine within the first 24 hours of life. Of 33 live born infants, 17 were not infected, 8 left the country prior to the 8-month serology test, 6 have serology pending (not yet 8 months) and 2 were lost to follow up. Conclusions: Treatment with LAM is a safe and effective. No vertical transmission of HBV was noted, and no adverse maternal or fetal effects were reported.